Faster Access to New Knowledge through Continuous Publication - Ravna, Øyvind (Arctic Review on Law and Politics, 2017)
Published: January 2017 Citation: Ø. Ravna. “Faster Access to New Knowledge through Continuous Publication.” Arctic Review on Law and Politics, Vol. 8, 2017, pp. 1–2. http://dx.doi.org/10.23865/arctic.v8.675